Clinical and radiological factors affecting progression in sarcoidosis - Aycicek, Olcay; Emiroglu, Ensar Cihat; Coban, Kadir; Erbay, Muge; Ozlu, Tevfik; Oztuna, Funda; Bulbul, Yılmaz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: To determine the clinical and radiological indicators of disease progression in a newly diagnosed sarcoidosis patient. Methods: The data of patients who were diagnosed with sarcoidosis in our department between January 2014 and June 2022 were analyzed. The patients were divided into two groups: progression and non-progression. Groups were compared according to symptoms at the time of diagnosis, comorbidities, foci of extrapulmonary involvement, shape, size, density, and localization of mediastinal lymph nodes, parenchymal findings, disease stage and whether or not treatment was received at the beginning. Results: The study included 292 sarcoidosis patients. The number of patients who progressed was 46 (15.8%). It was observed that stage II patients progressed more than stage I patients (p<0,001). The mean time to progression was 38.05±30.45 months in stage I and 28±58 months in stage II patients. Progression rate was higher in patients with right upper paratracheal, subaortic-paraaortic, subcarinal LAP (p= 0.010, p= 0.012, p= 0.020, respectively). The higher number of stations with LAP was associated with the presence of progression (p=0.017). The presence of parenchymal nodules (29/64.4%) and the number of lobes with nodules was also associated with progression (p= 0.027, 0.022, respectively). Progression rate was 76.1% in patients with treatment indication at the time of diagnosis (p<0.001). Conclusions: Disease stage is a prognostically important factor in the course of sarcoidosis, which is supported by our study results. Accordingly, it is important to follow patients with high-stage sarcoidosis more closely and to identify patients with treatment indications in time.